Effect of Chemotherapy and Hormonal Therapy on Bone Mineral Density in Patients with Breast Cancer in Saiful Anwar Hospital Malang - Nurshanty, Ade; Wardhani, Shinta Oktya; Suryana, Bagus Putu Putra (Clinical and Research Journal in Internal Medicine, 2020)
Osteoporosis is an important health problem, and the number of patients who suffered from it is increasing. Breast cancer is a condition that has aÂ  high risk of osteoporosis. Cancer induced bone disease results from the primary disease, metastatic process, or from therapies against the prime condition, causing bone fragility. Therefore, there are still different opinions regarding the therapeutic effect of breast cancer on bone mineral density. Aim: to determine the effect of chemotherapy and hormonal therapy on bone mineral density in patients with breast cancer in Saiful Anwar Hospital Malang. Method: this is a case-control study conducted in 30 patients with breast cancer who had undergone chemotherapy and hormonal therapy are compared to 30 patients without breast cancer as controls.Â  Bone Mineral Density (BMD) was measured by DEXA. Result: there are 53% of breast carcinoma patients having osteopenia and 13% having osteoporosis, with one patient has osteoporosis located in the femoral neck and three patients in lumbar (L1-L4). We obtain a significant T-score (p=0.02) in the great trochanter. Odds Ratio (OR) 0.233 with p = 0.008 showed a protective effect of chemotherapy and hormonal therapy for breast cancer to the bone density. Conclusion: the incidence of osteoporosis in the study was 13%, with the most location in the lumbar spine. Chemotherapy and hormonal therapy had a protective effect on BMD in patients with breast cancer in Saiful Anwar Hospital Malang.